THE INFLUENCE OF FISCAL DECENTRALIZATION, ORGANIZATIONAL COMMITMENT AND LEADERSHIP STYLE ON THE PERFORMANCE OF REGIONAL APPARATUS ORGANIZATIONS (OPD) - Trianda, Syahrial; Sukoharsono, Eko Ganis; Djamhuri, Ali (Accounting Department,, 2018)
This study aims to examine the effect of fiscal decentralization, organizational commitment and leadership style on OPD performance. This study uses a quantitative approach with explanatory research which is useful to analyze how a variable affects other variables for hypothesis testing. Respondents in this study were Head of OPD (Echelon II and Echelon III) in Batu City Government, Malang City, and Malang Regency. Sampling technique used by using Saturated Sampling Method, using survey method to 120 Head of OPD. This research uses Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis tool, with the help of WarpPLS 3.0 software. The result of hypothesis testing shows that fiscal decentralization has a positive effect on OPD performance. This means that with increased understanding of fiscal decentralization will be able to improve OPD performance. In terms of the type of leadership style itself shows good results and has a positive and significant effect on OPD performance. While the organizational commitment variable can not affect the performance of OPD.